Does Environmental Cost and Tax Aggressiveness Affect Minings Firm Value? - Lestari, Putri Gantine; Siregar, Johannes Kristian (Research Collaboration Community (Rescollacom), 2024)
Environmental problems caused by companies still occur in various countries. The environment that should be protected is still being ignored by surrounding companies. Even though it is clear in Indonesian Law, UU No. 40 2007 that all companies especially who are directly related to nature, are required to carry out environmental responsibility. Mining companies are companies whose business activities are directly related to nature, so the mining sector is obliged to carry out this responsibility. Environmental cost are cost incurred to environmental damage and environmental protection from company activities. The environmental cost will affect the good image of the company which will affect the firm value. Tax aggressiveness is an act of tax avoidance which is conducted aggressively and it’s also affect the firm value, these must be considered because the value of the company is one of the important information for stakeholders. The purpose of this research is to determine the effect of environmental cost and tax aggressiveness on firm value. The sample method used in this reseacrh is purposive sampling and obtained 80 financial statements from 20 mining companies listed on the Indonesian stock exchange for the 2018-2021 period. Based on the results of the research, partially that environmental cost have a significant positive effect on firm value, tax aggressiveness has no significant effect on firm value and simultaneously environmental cost and tax aggressiveness affect the value of mining companies listed on the Indonesian stock exchange for the 2018-2021 period.